From risk factors to detection and intervention: a metareview and practical proposal for research on cyberbullying - Ioannou, Andri; Blackburn, Jeremy; Siringhini, Gianluca; De Chrisiofaro, Emiliano; Kouriellis, Nicolas; Sirivianos, Michael; Zaphiris, Panayiotis (My University, 2017)
We sought to determine the level of maturity of the Cyberbullying research community and identify knowledge gaps that could be addressed in future projects in this area. Our findings suggest that the vast majority of academic contributions on cyberbullying focus on understanding the phenomenon, risk factors, and threats, with the prospect of suggesting possible protection strategies. The review calls for more research tackling the problem by leveraging statistical models and computational mechanisms geared to detect, intervene, and prevent cyberbullying. We argue that a multidisciplinary approach is needed for current challenges to be addressed and significant progress to be made, in order to combat this social menace.
Keywords: Cyber aggression; Cyberbullying; Internet bullying; Literature survey; Metareview; Research agenda; Social media